Divergent requirements for FGF signaling in zebrafish maxillary barbel and caudal fin regeneration - Duszynski, Robert J. (2013)
The zebrafish maxillary barbel is an integumentary organ containing skin, glands, pigment cells, taste buds, nerves, and endothelial vessels. The maxillary barbel can regenerate (LeClair & Topczewski, 2010); however, little is know about its molecular regulation. We have studied FGF-related signaling molecules during barbel regeneration, comparing these to a well-known regenerating appendage, the zebrafish caudal fin. Multiple FGF ligands (fgf20a, fgf24), receptors (fgfr1–4) and downstream targets (pea3, il17d) are expressed in normal and regenerating barbel tissue, confirming FGF activation. To test if specific FGF pathways were required for barbel regeneration, we performed simultaneous barbel and caudal fin amputations in two temperature-dependent zebrafish lines. Zebrafish homozygous for a point mutation in fgf20a, a factor essential for caudal fin blastema formation, regrew maxillary barbels normally, indicating that the requirement for this ligand is appendage-specific. Global overexpression of a dominant negative FGF receptor, Tg(hsp70l:dn-fgfr1:EGFP)(pd1) completely blocked fin outgrowth but only partially inhibited barbel outgrowth, suggesting reduced requirements for FGFs in barbel tissue. Maxillary barbels expressing dn-fgfr1 regenerated peripheral nerves, dermal connective tissue, endothelial tubes, and a glandular epithelium; in contrast to a recent report in which dn-fgfr1 overexpression blocks pharyngeal taste bud formation in zebrafish larvae (Kapsimali et al., 2011), we observed robust formation of calretinin-positive tastebuds. These are the first experiments to explore the molecular mechanisms of maxillary barbel regeneration. Our results suggest heterogeneous requirements for FGF signaling in the regeneration of different zebrafish appendages (caudal fin vs. maxillary barbel) and taste buds of different embryonic origin (pharyngeal endoderm vs. barbel ectoderm).